THE PHENOMENON OF LEADERSHIP IN CONGLOMERATE SUBSIDIARIES IN CREATING ANTI-FRAUD CULTURE - Mustika Prabaningrum Kusumawati; Ari Nur Rahman; Panzi Aulia Rahman (Asia Pacific Fraud Journal, 2018)
Leadership is a process of influencing leaders and followers to achieve organizational goals through change, where there are elements of Leader-Followers, Influence, Organizational Objectives, Change, and People. The existence of a corporate conglomerate can create an interconnected fraud link between conglomerate subsidiaries. Two main factors are the strong culture of nepotism and mental readiness of the heads of subsidiaries which are usually mostly employees placed from the holding company.Being a whistleblower is a step to get to a tiger cage, so if one of the tigers can be caught, then the other tiger is ready to pounce and make it a meal. One factor of ineffectiveness of the whistleblowing system (WBS) as part of the internal company or state institution, is the low level of employee or community participation due to fear of the consequences of being a whistleblower, so whistleblowing system (WBS) only becomes a system contained within a company to qualify for GCG sustainability.The ineffectiveness of the whistleblowing system (WBS) and the occurrence of social inequality, especially on income or salary among employees of the same rank, but having the background as the genuine employees of subsidiaries with former employees or placements of the holding company can create intentions to commit fraud or corruption within the internal conglomerate subsidiaries.